GENDER ROLES WITHIN THE FAMILY: TRADITION AND TRANSITION - JABBAROV, ULUGBEK (Журнал иностранных языков и лингвистики, 2024)
This article explores the evolution of gender roles within the family, tracing the historical context of traditional roles and examining the significant shifts that have occurred in the 20th and 21st centuries. Rooted in patriarchal structures, traditional family roles often assigned men as breadwinners and women as caretakers. However, social, economic, and political changes, including the women’s suffrage movement, the world wars, and the rise of feminism, have redefined these roles. The modern family is increasingly characterized by egalitarian dynamics, with both partners sharing responsibilities in the public and private spheres. This article also delves into contemporary issues such as the involved father, gender equality in household labor, and the impact of education on shaping more equitable family structures. Despite progress, challenges such as the unequal division of domestic labor persist, highlighting the ongoing journey toward true gender equality within the family. Through historical and modern lenses, this analysis underscores the complex interplay between tradition and transition in shaping gender roles.